Phenomenal role of nitroglycerin in the treatment of neonatal digital gangrene - Rahul Choudhary; Susil Choudhary; Garima Sachdeva; Arti Maria (Wolters Kluwer Medknow Publications, 2021)
Introduction: Placement of peripheral venous catheter is a common requirement for the neonates requiring intensive care unit admissions. This simple procedure can sometimes lead to catastrophic complications such as peripheral tissue ischemia/gangrene. This is particularly common in preterm neonates. Effective treatment is very important to prevent long-term sequelae or need for amputation. Nitroglycerin (NTG) is a potent smooth muscle relaxant and improves vascular flow. Case Report: Here, we report a case of neonatal digital gangrene which was successfully treated with topical NTG with no adverse outcome. Discussion: Topical NTG is a potential treatment option for neonatal peripheral gangrene.